Impact of a Multifaceted Intervention on Antibiotic Prescribing for Cystitis and Asymptomatic Bacteriuria in 23 Community Hospital Emergency Departments. (August 2023) - Ingalls, Emily M.; Veillette, John J.; Olson, Jared; May, Stephanie S.; Dustin Waters, C.; Gelman, Stephanie S.; Vargyas, George; Hutton, Mary; Tinker, Nick; Fontaine, Gabriel V.; Foster, Rachel A.; Stallsmith, Jena; et al.
Background: Urinary tract infections (UTIs) are over-diagnosed and over-treated in the emergency department (ED) leading to unnecessary antibiotic exposure and avoidable side effects. However, data describing effective large-scale antimicrobial stewardship program (ASP) interventions to improve UTI and asymptomatic bacteriuria (ASB) management in the ED are lacking.Methods: We implemented a multifaceted intervention across 23 community hospital EDs in Utah and Idaho consisting of in-person education for ED prescribers, updated electronic order sets, and implementation/dissemination of UTI guidelines for our healthcare system. We compared ED UTI antibiotic prescribing in 2021 (post-intervention) to baseline data from 2017 (pre-intervention). The primary outcomes were the percent of cystitis patients prescribed fluoroquinolones or prolonged antibiotic durations (>7 days). Secondary outcomes included the percent of patients treated for UTI who met ASB criteria, and 14-day UTI-related readmissions.Results: There was a significant decrease in prolonged treatment duration for cystitis (29% vs 12%, P  < .01) and treatment of cystitis with a fluoroquinolone (32% vs 7%, P  < .01). The percent of patients treated for UTI who met ASB criteria did not change following the intervention (28% pre-intervention versus 29% post-intervention, P   =  .97). A subgroup analysis indicated that ASB prescriptions were highly variable by facility (range 11%-53%) and provider (range 0%-71%) and were driven by a few high prescribers.Conclusions: The intervention was associated with improved antibiotic selection and duration for cystitis, but future interventions to improve urine testing and provide individualized prescriber feedback are likely needed to improve ASB prescribing practice.